2016
DOI: 10.18632/oncotarget.12786
|View full text |Cite
|
Sign up to set email alerts
|

Bruton tyrosine kinase inhibitor ONO/GS-4059: from bench to bedside

Abstract: The Bruton tyrosine kinase (BTK) inhibitor, ibrutinib, has been approved for the treatment of chronic lymphocytic leukemia, mantle cell lymphoma, and Waldenstroms macroglobulinemia. Acquired resistance to ibrutinib due to BTK C481S mutation has been reported. Mutations in PLC?2 can also mediate resistance to ibrutinib. Untoward effects due to off-target effects are also disadvantages of ibrutinib. More selective and potent BTK inhibitors (ACP-196, ONO/GS-4059, BGB-3111, CC-292) are being investigated. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Ono/GS-4059 has been evaluated in DLBCL and MCL cell lines in combination with other agents. Ono and phsophotidylinositol 3 kinase inhibitor idelalisib showed synergistic activity in inhibiting the growth of a subset of these cell lines [ 37 ]. In a phase 1 clinical trial, Ono demonstrated a 92% (11 of 12) overall response rate in patients with MCL [ 38 ].…”
Section: Treatment Of Mantle Cell Lymphomamentioning
confidence: 99%
“…Ono/GS-4059 has been evaluated in DLBCL and MCL cell lines in combination with other agents. Ono and phsophotidylinositol 3 kinase inhibitor idelalisib showed synergistic activity in inhibiting the growth of a subset of these cell lines [ 37 ]. In a phase 1 clinical trial, Ono demonstrated a 92% (11 of 12) overall response rate in patients with MCL [ 38 ].…”
Section: Treatment Of Mantle Cell Lymphomamentioning
confidence: 99%
“…11 More selective and potent BTK inhibitors are currently being investigated clinically. 3,12,13 CC 292 is a potent, selective, orally administered small-molecule inhibitor of BTK. CC 292 inhibits BTK activity by binding with high affinity to the adenosine triphosphate binding site of BTK and forming a covalent bond with the target BTK protein, providing rapid, complete, and prolonged inhibition of BTK activity, both in vitro and in vivo.…”
mentioning
confidence: 99%
“…As mentioned earlier, intratumoral injection of poly I:C slowed tumor progression (Salmon et al, 2016), an effect that may be due to activation of TLR3-expressing CD103 + cDC1s in the TME. In addition, imiquimod, a TLR7 agonist, is an approved therapy for basal cell carcinoma, implicating pDC stimulation and production of IFN-Is as important in anti-tumor activity (Le Mercier et al, 2013;Wu et al, 2017). Others TLR agonists are in clinical trials or have been approved for use in cancer; this topic is covered in greater detail in an earlier review (Shi et al, 2016).…”
Section: Ifn-i-stat1 Tlr and Sting Signaling In Dcs In The Tmementioning
confidence: 99%
“…For example, human pDCs activated by imiquimod or IFN-α, were able to lyse multiple human melanoma cell lines ex vivo (Kalb et al, 2012). Moreover, murine pDCs activated with either imiquimod or CpG (a TLR9 agonist) showed direct cytotoxic effects on mouse breast cancer cells in vitro, and suppressed tumor growth in vivo (Wu et al, 2017). Given the cytotoxic effects of IFN-Is, it is possible these responses result directly from pDC-mediated IFN-I production, although alternative mechanisms may also contribute.…”
Section: Roles For Pdcs In Solid Tumorsmentioning
confidence: 99%